The Determinants of Firm Value in Indonesia Stock Exchange - Agustini Hamid; Lulu Elika (Institute of Computer Science (IOCS), 2022)
We re-examined the determinant firm value of 274 public companies listed in Indonesia Stock Exchange from 2011 to 2020. Companies use market to book ratio to compare a firm's market capitalization to its book value. We augmented a new investment variable trend Environmental, Social, and Governance (ESG) disclosure, research and development voluntary disclosure whether the variables impact public companies' firm value. We also used dividend policy and liquidity on firm value. Panel data regression is used in our analysis. Regression results indicate that ESG and research and development have a positive and significant impact on firm value, while dividend and liquidity policies do not affect firm value.